Kinetic-dynamic modeling of co-composting of oil palm empty fruit bunch with rabbit manure in a closed system with mass and energy transfer - Talib, Ahmad Tarmezee (2015)
This study has two major purposes i.e. first is to determine the effect of different aeration rates on the organic matter (OM) degradation during the active phase of oil palm empty fruit bunch (EFB)-rabbit manure co-composting process; and secondly is to propose a kinetic-dynamic modeling with mass and energy transfers for EFB-rabbit manure co-composting process. Four different aeration rates, 0.13 L min-1 kgDM-1, 0.26 L min-1 kgDM-1, 0.49 L min-1 kgDM-1 and 0.74 L min-1 kgDM-1 were applied. 0.26 L min-1 kgDM-1 aeration rate performed better than other aeration rates which had 40.46 ± 0.52% of OM loss, highest C/N ratio reduction (49.57%), and the provided enough oxygen level i.e. higher than 10% for the rest of composting period. 0.49 L min-1 kgDM-1 and 0.74 L min-1 kgDM-1 aeration rates show similar trend in oxygen concentration, temperature profile and OM loss, suggesting that application of higher aeration rate for this compost system was not necessary. By taking into consideration of mass balance of water,gas balance and also energy balance, the thesis then proposes a dynamic mathematical model describing OM degradation, based on the ratio between OM content and initial OM content (OM i f ) with correction functions for moisture content ( F1), free air space ( FAS k ), oxygen (kO2 ) and temperature ( i fT) as follows: d OM OM d OM0 OM mti m ki fi fini =− ⋅ ⋅+ Model fitting were measured using relative root mean squared error (rRMSE) analysis and shows a good result with the accuracy of model used in this study is comparable with other model found in the literature. The result of sensitivity analysis shows that temperature and degradation of OM within composting system were more affected by insufficient oxygen supply due to the lower aeration rates than loss of heat by high energy transfer out from the system due to the higher aeration rates.